(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Up to 2% of the population is affected with alopecia areata (AA), a prevalent chronic tissue-specific autoimmune disease that causes hair loss. The specific pathobiology of AA is still unknown, however the most widely accepted idea is that an immunological process led the hair follicle's immune privilege to collapse. The etiology of AA is influenced by numerous environmental and genetic variables. One or more well-defined patches, more diffuse or total hair loss of the scalp (alopecia totalis), or hair loss of the entire body are all clinically treated for AA using a variety of clinical approaches (alopecia universalis). Corticosteroids and other immunomodulators, minoxidil, and contact immunotherapy are some of the available treatments for AA.